Dietary Supplementation with Fish Oil or Conjugated Linoleic Acid Relieves Depression Markers in Mice by Modulation of the Nrf2 Pathway. Issue 21 (2nd September 2019) - Cigliano, Luisa; Spagnuolo, Maria Stefania; Boscaino, Floriana; Ferrandino, Ida; Monaco, Antonio; Capriello, Teresa; Cocca, Ennio; Iannotta, Lucia; Treppiccione, Lucia; Luongo, Diomira; Maurano, Francesco; Rossi, Mauro; et al.
Abstract: Inflammation and oxidative stress play an important role in the pathogenesis of depressive disorders and nuclear erythroid related factor 2 (Nrf2), a regulator of RedOx homeostasis and inflammation, is a promising target for depression prevention/treatment. As fish oil (FO) and conjugated linoleic acid (CLA) are known Nrf2 inducers, their protective ability is comparatively evaluated in a murine model of depression (MRL/MpJ‐Fas lpr ). Oxidative stress, fatty acids content, and critical factors reflecting brain functioning—namely brain‐derived neurotrophic factor (BDNF), synaptic markers, and cholinergic signaling—are preliminarily evaluated in the frontal cortex of 8‐week (Young) and in 22‐week old animals (Old), which are used as model of depression. These markers are measured in Old mice at the end of a 5‐week pretreatment with FO or CLA (728 or 650 mg kg –1, respectively). Old mice exhibit disrupted Redox homeostasis, compensatory Nrf2 hyperactivation, lower docosaheaxaenoic acid (DHA), and lower BDNF and synaptic function proteins compared to Young mice. FO and CLA treatment relieves almost all the pathophysiological hallmarks at a level comparable to Young mice. Presented data provide the first evidence for the comparable efficacy of FO or CLA supplementation in preventing depression signs in Old MRL/lpr mice, likely through their ability of improving Nrf2‐mediated antioxidant defenses. Abstract : Nuclear erythroid related factor 2 (Nrf2) is a regulator of antioxidant/detoxifying defenses and a promising target for depression prevention/treatment. Fish oil (FO) or conjugated linoleic acid (CLA) intake prevents several crucial signs of depression (brain Nrf2 hyperactivation, declined DHA and BDNF content). FO or CLA ability to activate Nrf2 pathway is at least in part accountable for their antidepressant effect.